Exaggerated Narrations in Content Commodification : Between Maintaining Power and Its Potential Implication to The Creator’s Public Image in Indonesia’s YouTube Industry - Santika, Azzumar Adhitia; Alvina, Yasmin (Journal of Communication and Public Relations, 2025)
Recent commodification studies tend to pay more attention to what is commodified but less to exaggerated narration that aims to boost the process specifically, particularly in Indonesia’s YouTube industry. This study aims to deconstruct how Atta Halilintar (AH), a top Indonesian YouTuber, uses exaggerated narrations as an extra flavor in his commodification practice in order to manage his power in the industry. Using Vincent Mosco’s view on commodification and multimodal critical discourse analysis framework, this study reveals how those exaggerated narrations are embedded in various aspects of the content such as titles, thumbnails, photography compositions, and conversations. The result of this study shows that AH exaggerated the narrations in his content to make it more enjoyable and subsequently easier to market both to the audience and advertising messages, no matter if the information is truly valid or not. Eventually, this action can be seen as an attempt by the content creator to do their political economy of communication agenda in the context of Indonesia’s YouTube industry, which is to help the content creator keep his power. As a consequence, this action at some point can harm the doer’s public image since there is an impression that they tend to neglect ethical values just for their political economy agenda. Thus, exaggerated narrations should get more attention in the future commodification of content studies due to insufficient conceptual exploration.